Upaya Pencegahan Faham Radikalisme dan Terorisme melalui Kearifan Lokal Di Sumatera Selatan - Isabella Isabella; Periansyah Periansyah (Jurnal Pemerintahan dan Politik, 2021)
There are still many acts of terrorism in Indonesia which is clear evidence that a security approach is not effective enough to eradicate terrorism and radicalism to its roots. South Sumatra Province itself in 2019 was at 37.33 percent or in the low category. However, even though it is in a low category, the people of South Sumatra cannot just let their guard down with the potential for radicalism and terrorism. Because in a short time this condition could change. For this reason, efforts to prevent the spread of radicalism and terrorism are necessary. Therefore, various approaches to dealing with terrorism and other radicalism must also be pursued. For example, through developing culture in each area or what is known as local wisdom. Local wisdom in Indonesia is too interesting to discuss. Including local wisdom in South Sumatra. One of the local wisdoms in South Sumatra includes speech culture. This study aims to examine the role of local wisdom in efforts to prevent radicalism and terrorism. The method used in this research is descriptive qualitative, by interviewing several expert informants who understand local wisdom and efforts to prevent radicalism and terrorism. It is hope that this research can become a reference for other research related to the prevention of radicalism and terrorism through local wisdom. The results of this study indicate that local wisdom provides an important role and learning in efforts to prevent radicalism and terrorism. Keyword : local wisdom, radicalism, terrorism